Tre pointer fra Grue-Sørensen til nutidens pædagogik - Laursen, Per Fibæk (Studier i Pædagogisk Filosofi, 2018)
When K. Grue-Sørensen became a professor of pedagogy at the University of Copenhagen in 1955, he was in line with the dominant historical-hermeneutical approach to humanities. From the late 1960s until retirement in 1974, his approach was challenged by both technical and critical alternatives. Both these alternative have since grown steadily, while the historical-hermeneutical view has been in the defensive. But Grue-Sørensen and the tradition he represented have three signifi cant points for today’s pedagogy, whether it is technical or critical: pedagogy can and should not deliver effi ciency technology, pedagogy should as far as possible use everyday language, and fi nally that the educational history can make us wiser.